A Institucionalização das relações civis-militares no Brasil (1988-2014): o papel das prerrogativas presidenciais - Barreto, Lis (2021)
The presented research aimed to identify the causal mechanism that allowed for the institutionalization of the Brazilian civil-military relations between 1988 and 2014. First, there was a need to demonstrate the occurrence of such a process, through a comparative analysis of the existing legislation in 1988 and 2014, showing whether they had become more complex, circumscriptive, and universalist during that time. Once the institutionalization process had been confirmed, process-tracing techniques were used to deduce the process, identifying the patterns of institutional change and, therefore, collecting information that would help identify the causal mechanism. The proceedings of the Constitutional Emends and Complimentary Laws, and theme-related policies were analyzed, and the findings were qualified in light of the concepts of Historical Institutionalism. Such findings allowed for the identification of the predominant action coming from the Executive Power in the institutional modifications, and for the determination of which resources available to this Power enabled it to act in such a dominant manner. Making use of the literature on the Brazilian Presidentialism, it was possible to understand what are the presidential prerogatives, and in which way they have provided advantage to the President, enabling a legislative predominance of the Executive Power in multiple areas, including civil-military relations. Such prerogatives were divided into three types, according to what was found: precedence, resources and tools – and, with them, it was possible to deduce the causal mechanism that allowed for the institutionalization of the civil-military relations between 1988 and 2014.